RAPA'I UROH DALAM ARAK-ARAKAN KAMPANYE DAMAI ACEH TAHUN 2005 - Dharminta Soeryana (Pascasarjana Institut Seni Indonesia Surakarta, 2009)
After tsunami, Aceh culture experienced very rapid development, especially rapa’i uroh music which had ever halted due to armed conflict. The Procession of Aceh peace campaign on 7-8 August 2005 by attending rapa’i uroh music which carry- ing of Aceh peace campaign is the first rise of the existence of rapa’i uroh music in NAD province.In the use of rapa’i uroh music in the context of procession that carrying the Aceh peace campaign, there are some part obtaining benefits as useful value, such as social value, emotional expression and raises nationalism values, namely: the group of the rapa’i artist itself, the holders (the local and the central government), and large Acehnese society.In the use of the useful value of the rapa’i uroh music in the procession that carry- ing the Acehnese peace campaign, there are some functions that can be obtained: As Image, expressing emotion, communication, integrity and cultural symbol.In order this writing contains annalistic explanation, it is required that idea meth- ods and system with borrowing the concepts of culture, music, integration and social community to find the symptoms from procession that carrying Aceh peace campaign On 7-8 August 2005. Keywords: Rapa’i uroh, procession, peace campaign